"Everybody's Really Close-Knit": Disconnections Between Helping Victims of Intimate Partner Violence and More General Helping in Rural Communities. (March 2019) - Banyard, Victoria L.; Edwards, Katie M.; Moschella, Elizabeth A.; Seavey, Katherine M.
Social support is key to well-being for victims of intimate partner violence (IPV), and bystanders have an important role to play in preventing IPV by taking action when there is risk for violence. The current study used qualitative interviews to explore young adults' perspectives on helping in situations of IPV, and more general helping, in the rural communities in which they resided. Participants were 74 individuals between the ages of 18 and 24 years from 16 rural counties across the eastern United States. Participants generally described their communities as close-knit and helpful, especially around daily hassles (e.g., broken down car) and unusual circumstances (e.g., house fire). Although participants generated ways in which community members help IPV victims, these mostly focused on providing support or taking action in the aftermath of IPV as opposed to more preventive actions. Lack of financial resources were uniquely cited as a barrier to more general helping, whereas concerns about privacy and lack of deservingness of help were barriers to both general helping and helping in IPV situations, although these were more pronounced in IPV situations than general helping situations. Taken together, these results suggest that although people generally see their communities as helpful and close-knit, these perceptions and scripts did not necessarily translate to helping in situations of IPV. Bystander intervention programs are needed that provide more specific helping scripts for IPV.